Metal–polydopamine frameworks and their transformation to hollow metal/N-doped carbon particles. Issue 16 (11th April 2017) - Liang, Y.; Wei, J.; Hu, Y. X.; Chen, X. F.; Zhang, J.; Zhang, X. Y.; Jiang, S. P.; Tao, S. W.; Wang, H. T.
Abstract : A "MOF genetic" strategy was developed to form hollow metal–organic structures from MOF crystals and dopamine, providing a simple and effective way to synthesize hollow metal/N carbon materials as high-performance oxygen reduction reaction electrocatalysts. Abstract : We present a new strategy for in situ transformation of metal–organic framework (MOF) crystals to hollow metal–organic structures through polycondensation of dopamine. The hollow metal–polydopamine (PDA) particles are formed by a coordination assembly of metal ions (Co and Zn) and PDA, inheriting the morphology of MOF (ZIF-67 and ZIF-8) crystals. The hollow porous metal/N-carbon particles morphosynthetically transformed from hollow metal–PDA particles exhibit excellent oxygen reduction electrocatalytic activity. The strategy presented here is promising for synthesizing hollow metal–organic polymer (metal–carbon) particles with diverse morphologies for energy and environmental applications.